Perfusão cerebral e análise individual automatizada utilizando SPECT em uma população com transtorno obsessivo-compulsivo - da Rocha, Euclides Timóteo [UNESP]; Buchpiguel, Carlos Alberto; Miguel, Euripedes Constantino; Peres, Stela Verzinhase; Filho, Geraldo Busatto (FapUNIFESP (SciELO), 2011)
Objective: To make individual assessments using automated quantification methodology in order to screen for perfusion abnormalities in cerebral SPECT examinations among a sample of subjects with OCD. Methods: Statistical parametric mapping (SPM) was used to compare 26 brain SPECT images from patients with OCD individually with an image bank of 32 normal subjects, using the statistical threshold of p < 0.05 (corrected for multiple comparisons at the level of individual voxels or clusters). The maps were analyzed, and regions presenting voxels that remained above this threshold were sought. results: Six patients from a sample of 26 OCD images showed abnormalities at cluster or voxel level, considering the criteria described above, which represented 23.07%. However, seven images from the normal group of 32 were also indicated as cases of perfusional abnormality, representing 21.8% of the sample. Conclusion: The automated quantification method was not considered to be a useful tool for clinical practice, for analyses complementary to visual inspection.
Cerebral perfusion and automated individual analysis using spect among an obsessive-compulsive population
Keywords: Brain SPECT; Individual analysis; OCD; SPM; cysteine ethyl ester tc 99m; adult; automation; brain mapping; brain perfusion; clinical article; clinical assessment; controlled study; female; human; image processing; male; obsessive compulsive disorder; prediction; single photon emission computer tomography